Multidisciplinary Management of Depression in Patients with Chronic Illness: Integrating Psychological, Nutritional, Nursing, and Digital Health Approaches - Shehab, Aiman Ali Ebrahem; Moafa, Abdulrahman Ahmed Mohammed; Kamili, Mohammed Othman Ibrahim; Shehab, Alaaldeen Ahmed Ibrahim; Moafa, Mohammed Ahmed M; Muallim, Ibrahim Mohammed Ali; Sahli, Khalid Mohammed Ali; Aljafery, Nasser Mohsen Nasser; Hakami, Anwar Ali; Al-Juhani, Akram Abdulkarim; Sweidi, Fahad Ali Mohammad; Hamzi, Adel Mohammed Mousa (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Major Depressive Disorder (MDD) is a highly prevalent condition that frequently co-occurs with chronic medical illnesses, creating a synergistic burden that worsens quality of life, impairs treatment adherence, and increases mortality. The relationship is bidirectional, with medical illness increasing depression risk and depression contributing to the onset and progression of somatic disease. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to review the multidisciplinary management of depression in medically ill patients, integrating psychological, pharmacological, nursing, social, and digital health approaches to improve detection and treatment outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> The review synthesizes epidemiological data, pathophysiological mechanisms (including shared genetics, inflammation, and neurobiological pathways), and evidence from clinical trials and meta-analyses. It evaluates diagnostic challenges, screening tools, and a range of management strategies, including pharmacotherapy (with attention to drug-disease interactions), psychotherapy, neuromodulation, and collaborative care models. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> Depression is prevalent across chronic conditions like cancer, cardiovascular disease, and diabetes, with rates often exceeding 20%. Effective management requires an integrated, etiology-driven approach. Antidepressants and adapted psychotherapies demonstrate efficacy, but success depends on careful agent selection to avoid adverse interactions. Collaborative care models, which systematize screening and combine a care manager with psychiatric oversight, consistently yield the best functional and symptomatic outcomes. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; vertical-align: baseline; white-space-collapse: preserve;"> A multifaceted, patient-centered strategy that coordinates medical and mental healthcare is essential. Success hinges on moving beyond simple screening to embed management within a structured, multidisciplinary framework that addresses the complex biological, psychological, and social interplay between depression and physical illness.